HEALTH STATUS AND LIFESTYLE OF CHILDREN FROM DISADVANTAGED FAMILIES - V.Yu. Al'bitskiy; S.Ya. Volgina; E.A. Kurmaeva (Вопросы современной педиатрии, 2007)
The article analyzes the documents of the international organizations, data of the Russian and foreign authors devoted to poverty and health of children from disadvantaged families. It was shown that poverty is the basic risk factor for the somatic and psychic disorders of children. The reduction of the impact exerted by the given factor on the health status of children may be achieved by the multidisciplinary approach only.Key words: child, poverty, health, lifestyle.